Chasing a moving target: perceptions of work readiness and graduate capabilities in music higher research degree students. Issue 2 (11th January 2016) - Harrison, Scott; Grant, Catherine
Abstract : Recent efforts to increase workplace readiness in university students have largely centred on undergraduates, with comparatively few strategies or studies focusing on higher research degree candidates. In the discipline of music, a wide diversity of possible career paths combined with rapidly changing career opportunities makes workplace readiness a moving target. Drawing on qualitative and quantitative data from semi-structured interviews, dialogue forums, an online survey and pre-existing literature, this paper explores perceptions of higher degree research (HDR) music students about their work readiness, and critically examines these perceptions against graduate capabilities frameworks. It recommends ways to better prepare HDR music students for life beyond their studies, advocating in particular a more collaborative model of research education than is currently the norm. The findings may help improve the student experience and graduate outcomes among HDR students, both in music and more broadly.